Pengaruh Head dan Jumlah Nozzle terhadap Kinerja Turbin Pelton Skala Laboratorium - Supriatno Supriatno; Djoko Setyanto (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This experimental study examines the influence of hydraulic head and nozzle number on the performance of a laboratory-scale Pelton turbine. A closed-loop test rig was developed, enabling operation with one, two, and four nozzles. The turbine, consisting of 12 buckets, was mechanically coupled to an electrical generator through a belt–pulley transmission. Experimental results reveal that increasing the number of nozzles enhances turbine efficiency, with recorded values of 2.8%, 15.8%, and 17.7% for single-, double-, and four-nozzle configurations, respectively. Despite this improvement, the turbine failed to operate at its optimal efficiency, primarily due to discrepancies between the available head and the turbine design parameters, as well as energy losses and suboptimal jet impingement.